IMPLEMENTASI ADVANCED DRIVER ASSISTANCE SYSTEM MENGGUNAKAN METODE SURF DALAM MENGENALI RAMBU-RAMBU LALU LINTAS DI INDONESIA - Yudha Pratama; Agus Virgono; Fussy Mentari Dirgantara (POLITEKNIK NEGERI JAKARTA, 2021)
Technology to detect traffic signs is made based on awareness to prioritize compliance with driving regulations. There are still many who do not understand what each traffic sign means. With the advanced driver assistance system (ADAS), it is hoped that they will be able to provide solutions that can help the public in understanding traffic signs in Indonesia, especially traffic warning signs. ADAS is useful for detecting traffic signs in front of us when we drive. The speeded-up robust features (SURF) method can be used to detect traffic signs This implementation aims to reduce the number of accidents due to driver's lack of awareness of traffic signs in Indonesia. The highest detection accuracy of SURF with Hessian Threshold 350 is 33.3%, with Hessian Threshold 500 is 23%, and accuracy with Hessian Threshold 750 is 15.3% with average FPS are 7.5 FPS, 10.5 FPS, and 13 FPS, respectively.